2012
DOI: 10.1515/jpm-2011-0233
|View full text |Cite
|
Sign up to set email alerts
|

No “masculinization” effect of a male on birth weight of its female co-twin

Abstract: After exclusion of potential confounders and controlling for chorionicity, parity, and gestational age, our data do not support the presence of a "masculinization" effect on birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
(16 reference statements)
1
9
1
Order By: Relevance
“…A potential ‘masculinization’ effect with female co‐twins in an FM pair weighing more than a girl in an FF pair has been reported previously . However, similar to the study reported by Tul et al ., we did not find any significant masculinization effect on the birthweight of the female co‐twin …”
Section: Discussioncontrasting
confidence: 69%
“…A potential ‘masculinization’ effect with female co‐twins in an FM pair weighing more than a girl in an FF pair has been reported previously . However, similar to the study reported by Tul et al ., we did not find any significant masculinization effect on the birthweight of the female co‐twin …”
Section: Discussioncontrasting
confidence: 69%
“…Some studies have reported that females from OS twin pairs show an increased tooth size (28), adverse anthropometric, and metabolic parameters (15), increased alcohol use disorder symptoms (29), increased risk for alcohol dependence (30), greater sensation seeking (31), and enhanced aggressive behaviors (32) as compared to female twins from SS twin pairs. However, the present literature is far from consistent, and negative reports exist for several traits, including, anthropometric measures (33), birth weight (34), disordered eating (35, 36), and fertility (27). …”
Section: Discussionmentioning
confidence: 87%
“…Transfer of testosterone is assumed, based on animal studies of intrauterine position, but these studies show that masculinization is most likely for female foetuses that gestate between two male foetuses, with smaller effects for those that gestate next to just one male foetus (Ryan and Vandenbergh, 2002), raising scepticism about sufficient hormone transfer in human pregnancies to affect physiology or behaviour. The literature is far from consistent and recent studies fail to see masculinization for a variety of personality and fertility traits such as anthropometric measures and fertility (Korsoff et al, 2014), birth weight (Sorensen et al, 2013; Tul et al, 2012), eating disorders (Lydecker et al, 2012), and age at menarche (Sorensen et al, 2013). However, the recent review on OS vs SS studies (Tapp et al, 2011) found the most consistent evidence for hormonal transfer in studies investigating cognitive traits in line with recent evidence from clinical studies linking early androgen exposure to spatial abilities (Puts et al, 2008).…”
Section: Discussionmentioning
confidence: 99%